The Preparation for Musical Performance by Guitar Quartet from the point of view by Professional Guitarists (Per Musi, 2023)
In this article, strategies for chamber music performance by guitar quartets were raised and discussed, considering the point of view Brazilian Professional Guitarists. The study was developed based on authors who deal with musical performance planning and discuss performance preparation techniques and procedures, especially for chamber music. Through a questionnaire applied to guitarists who work and have worked in Brazilian Quartets, we sought to raise rehearsal strategies applied to practice by these groups, through questions about the planning and performance of their rehearsals, techniques and strategies for individual and collective study, availability of time, interpersonal relationships and integrations and musical interpretation, and their interactions. The analysis of the compiled material showed the most used procedures in their practices, and presented guidelines for their optimization, contemplating specificities of the chamber music of the guitar quartet.